Conductive agent, method for preparing the same and use thereof
Patent Information
- Application Number
- CN202611069122.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-13
AI Technical Summary
[0005]本申请提供了一种导电剂及其制备方法和应用,以解决现有技术中碳基导电网络在弯折时易断裂、液态金属在碱性电解液中易发生氧化反应且物理混合结构无法形成稳定导电网络的问题
1、通过碳基骨架对镓基液态金属的物理约束作用,使镓基液态金属表观粘度提升约104倍,有效抑制了动态弯折过程中镓基液态金属的流动与聚集,实现了10万次弯折循环后电阻增幅<5%的优异机械稳定性,解决了传统碳基导电网络在弯折时易断裂的技术问题。
Smart Images

Figure CN122907636A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of composite conductive materials technology, specifically to a conductive agent, its preparation method, and its application. Background Technology
[0002] As a key component of flexible battery electrodes, conductive agents not only need to provide efficient electron transport channels but also must maintain structural integrity and conductivity stability during repeated bending. Currently, conductive agents for flexible electrodes mainly employ carbon-based conductive networks (such as carbon nanotubes) or liquid metal-based conductive materials. Although carbon-based conductive networks exhibit good chemical stability, they are prone to slippage and breakage during dynamic mechanical deformation, leading to network failure and failing to meet the long-term use requirements of flexible batteries.
[0003] Liquid metals (such as gallium-based alloys) have attracted widespread attention due to their intrinsic fluidity and high conductivity. However, liquid metals are prone to electrochemical corrosion in aqueous electrolyte environments, leading to performance degradation. Existing technologies mainly employ polymer coating strategies, but the polymer insulating layer severely hinders electron transport, causing a significant decrease in the conductivity of the composite material, which cannot meet high-power requirements. Furthermore, existing liquid metal / carbon composite materials mostly use physical mixing methods, with the liquid metal existing as a discrete phase and lacking effective interfacial bonding with the carbon framework. This results in easy phase separation during dynamic deformation and an inability to suppress corrosion behavior, leading to poor long-term stability.
[0004] Therefore, there is an urgent need to develop a new type of flexible conductive agent that can effectively suppress network breakage and electrolyte corrosion during dynamic deformation while maintaining high conductivity, thereby achieving a synergistic improvement in the conductivity and mechanical stability of flexible batteries. Summary of the Invention
[0005] This application provides a conductive agent, its preparation method, and its application to solve the problems in the prior art where carbon-based conductive networks are prone to breakage when bent, liquid metals are prone to oxidation reactions in alkaline electrolytes, and physically mixed structures cannot form stable conductive networks.
[0006] In a first aspect, this application provides a conductive agent comprising a carbon-based framework and a gallium-based liquid metal continuous network spread along the surface of the carbon-based framework; an oxide layer is formed on the surface of the gallium-based liquid metal, and the oxide layer is connected to the carbon-based surface by gallium-oxygen-carbon covalent bonds to form an interpenetrating network structure.
[0007] In some embodiments, the carbon-based framework comprises carbon nanofibers.
[0008] In some embodiments, the carbon nanofibers comprise cellulose nanofibers.
[0009] In some embodiments, the cellulose nanofibers have a diameter of 15-25 nm, a length of >50 μm, and a degree of graphitization of >80%.
[0010] In some embodiments, the carboxyl content of the carbon-based skeleton is not less than 1.2 mmol / g.
[0011] In some embodiments, the gallium-based liquid metal includes at least one of gallium indium tin alloy, gallium indium alloy, and gallium tin alloy.
[0012] In some embodiments, the gallium content in the gallium-based liquid metal is ≥60wt%.
[0013] In some embodiments, the apparent viscosity of the gallium-based liquid metal at 25°C is ≥10. 4 Pa·s.
[0014] In some embodiments, the gallium-based liquid metal is spread along the surface of the carbon nanofiber framework to a thickness of 80-120 nm.
[0015] In some embodiments, the thickness of the oxide layer is 2-3 nm.
[0016] In some embodiments, the oxide layer includes at least one of Ga2O3 and GaOOH.
[0017] Secondly, this application provides a method for preparing the conductive agent described in the first aspect, comprising the following steps: Preparation of carbon-based hydrogels; The carbon-based hydrogel was mixed with gallium-based liquid metal droplets and then freeze-dried to form a porous composite aerogel. In an inert atmosphere, the porous composite aerogel is heat-treated at 145-155°C to melt the gallium-based liquid metal and spread it along the surface of carbon nanofibers, forming gallium-oxygen-carbon covalent bonds.
[0018] In some embodiments, the diameter of the gallium-based liquid metal droplets is 200-500 nm.
[0019] In some embodiments, the mass ratio of the gallium-based liquid metal droplet to the carbon-based hydrogel is 1:(1-3).
[0020] In some embodiments, the heat treatment time is 0.5-2 hours.
[0021] Thirdly, this application provides an electrode comprising an active material, a binder, and a conductive agent, wherein the conductive agent comprises the conductive agent described in the first aspect, and the amount of the conductive agent added is 3-6 wt%.
[0022] Fourthly, this application provides a battery that includes the electrodes described in the third aspect.
[0023] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. By physically confining gallium-based liquid metal with a carbon-based framework, the apparent viscosity of the gallium-based liquid metal is increased by approximately 10%. 4 This effectively suppresses the flow and aggregation of gallium-based liquid metal during dynamic bending, achieving excellent mechanical stability with a resistance increase of less than 5% after 100,000 bending cycles, and solving the technical problem of easy breakage of traditional carbon-based conductive networks during bending.
[0024] 2. A dense interfacial barrier was constructed through gallium-oxygen-carbon (Ga-OC) covalent bonds formed between the surface oxide layer and the carbon-based surface (XPS Ga3d peak at 20.2 eV), reducing the corrosion current density to <10 eV. -8 A / cm² can improve the chemical stability of the conductive agent in an alkaline aqueous electrolyte environment, overcoming the tendency of liquid metals to undergo 4Ga + 12OH in the battery working environment. - →2Ga₂O₃ + 6H₂O + 12e - Technical issues related to oxidation reactions.
[0025] 3. When mechanical bending causes local cracking of the oxide layer, the underlying gallium-based liquid metal can immediately flow to fill and repair it, giving the conductive agent a unique self-healing function and further extending the service life of the flexible electrode.
[0026] 4. The continuous conductive network formed by the in-situ spreading of gallium-based liquid metal along the surface of carbon nanofibers maintains metallic-grade high conductivity (conductivity > 10). 4 The conductivity of this technology (S / m) avoids the problem of a significant decrease in conductivity caused by existing polymer coating technology (conductivity of traditional technology <10³ S / m), and achieves synergistic optimization of high conductivity and mechanical stability, which is beneficial to improving the electrochemical performance of flexible aqueous batteries. Attached Figure Description
[0027] To more clearly illustrate the technical solutions in the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0028] Figure 1 The Ga 3d high-resolution XPS spectrum of the conductive agent prepared in Example 1.
[0029] Figure 2The images show the FTIR spectra of the gallium-based liquid metal surface oxide layer and the cellulose nanofiber interface before and after bonding in Example 1.
[0030] Figure 3 This is a comparison graph showing the increase in resistance during the bending cycle of the conductive agent in Examples 1, 4, and 5 and Comparative Examples 1-3.
[0031] Figure 4 This is a comparison graph of the potentiodynamic polarization curves of the conductive agents in Examples 1 and 5 and Comparative Example 2.
[0032] Figure 5 The graph shows a comparison of the electrochemical performance of the conductive agents in Examples 1-5 and Comparative Examples 1-3. Detailed Implementation
[0033] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below in conjunction with the embodiments of this application. Obviously, the described embodiments are only some, not all, of the embodiments of this application. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0034] As a core energy storage unit in wearable electronics, flexible energy storage devices and other fields, the performance of the conductive agent in flexible batteries directly determines the electrochemical stability of the battery under dynamic deformation conditions, and is a key material for the industrialization of flexible batteries.
[0035] The research and application of conductive agents for flexible batteries still face two major technological challenges: First, the dynamic stability of carbon-based conductive networks is insufficient. Conductive networks constructed from carbon-based conductive materials such as carbon nanotubes and graphene are prone to cracking or even breakage at the interfaces between carbon materials during dynamic deformation processes such as electrode bending and curling. This leads to damage to the conductive pathways and a sharp increase in the battery's internal resistance, failing to meet the requirements of repeated deformation in flexible batteries. Second, the corrosion and encapsulation contradictions of liquid metal conductive materials are prominent. Although gallium-based liquid metals possess high metallic conductivity, making them an ideal choice for flexible conductive agents, gallium alloys are prone to oxidation and corrosion reactions in aqueous electrolytes, especially alkaline aqueous electrolytes (reaction formula: 4Ga + 12OH). - → 2Ga₂O₃ + 6H₂O + 12e⁻ - This causes the loss of the metallic phase and the degradation of conductivity. Furthermore, existing anti-corrosion encapsulation technologies using polymer coatings form an insulating layer on the surface of the liquid metal, which significantly sacrifices the conductivity of the conductive agent, resulting in a conductivity generally below 10³ S / m, making it difficult to simultaneously achieve both corrosion resistance and high conductivity.
[0036] The applicant discovered that by using a carbon-based framework as the support structure, combined with a continuous network of gallium-based liquid metal spread along the surface of the carbon-based framework, and by forming an interpenetrating network structure through gallium-oxygen-carbon covalent bonds between the gallium-based liquid metal surface oxide layer and the carbon-based framework, a strong bond between the carbon-based framework and the gallium-based liquid metal can be achieved. The carbon-based framework can effectively constrain the free flow of the gallium-based liquid metal, increasing its apparent viscosity, while the gallium-oxygen-carbon covalent bonds can block direct contact between the electrolyte and the gallium-based liquid metal, solving its corrosion problem, while retaining the metallic conductivity of the gallium-based liquid metal. In addition, the liquid properties of the gallium-based liquid metal allow it to be filled and repaired in situ when the conductive network is damaged. Combined with the flexible mechanical properties of the carbon-based framework, the dynamic stability of the conductive agent can be improved.
[0037] In view of this, this application provides a conductive agent, its preparation method and application, to solve the problems in the prior art where carbon-based conductive networks are prone to breakage when bent, liquid metals are prone to oxidation reactions in alkaline electrolytes, and physical mixed structures cannot form stable conductive networks.
[0038] In a first aspect, this application provides a conductive agent, as described in the embodiments of this application, see below. Figure 1 The conductive agent includes a carbon-based framework and a gallium-based liquid metal continuous network spread along the surface of the carbon-based framework; an oxide layer is formed on the surface of the gallium-based liquid metal, and the oxide layer is connected to the carbon-based surface by gallium-oxygen-carbon covalent bonds to form an interpenetrating network structure.
[0039] In the conductive agent provided in this application, the physical constraint of the carbon-based framework on the gallium-based liquid metal can increase the apparent viscosity of the gallium-based liquid metal, effectively suppressing the flow and aggregation of the gallium-based liquid metal during dynamic bending. This results in a minimal increase in resistance after long-cycle bending, solving the technical problem of easy breakage of traditional carbon-based conductive networks during mechanical deformation. Furthermore, the gallium-oxygen-carbon covalent bonds formed between the oxide layer and the carbon-based surface construct a dense interfacial barrier, effectively blocking electrolyte penetration and improving the chemical stability of the conductive agent in alkaline aqueous electrolyte environments. This invention addresses the technical challenge of the oxidation reaction of gallium-based liquid metals. Furthermore, when mechanical bending causes localized cracking of the oxide layer, the underlying gallium-based liquid metal can immediately flow to fill and repair it, endowing the conductive agent with a unique self-healing function and further extending the lifespan of the flexible electrode. Finally, the continuous conductive network formed by the gallium-based liquid metal along the carbon-based framework maintains metallic-level high conductivity, overcoming the significant decrease in conductivity caused by the presence of an insulating layer in existing polymer coating strategies. This achieves synergistic optimization of high conductivity and mechanical stability, which is beneficial for improving the electrochemical performance of flexible aqueous batteries.
[0040] It should be explained that "interpenetrating network structure" refers to a composite structure in which a three-dimensional network formed by a carbon-based framework and a continuous conductive network formed by gallium-based liquid metal are intertwined and firmly bonded by covalent bonds.
[0041] It should be explained that "self-healing" refers to the characteristic that when the conductive agent is bent and the oxide layer breaks, the gallium-based liquid metal can fill the damaged area in situ and repair the conductive network.
[0042] In some embodiments of this application, the carbon-based framework includes carbon nanofiber-like one-dimensional carbon-based nanomaterials, and the carbon-based framework may also be carbon nanotubes, graphene, etc.; preferably, the carbon nanofibers include cellulose nanofibers; more preferably, the cellulose nanofibers are pyrolytic cellulose nanofibers (CNF). Using pyrolytic cellulose nanofibers as the carbon-based framework provides a wide availability and low cost of biomass-based raw materials, and after pyrolysis modification, it possesses high graphitization and excellent mechanical properties.
[0043] In some embodiments of this application, the cellulose nanofibers have a diameter of 15-25 nm, a length >50 μm, and a graphitization degree >80%; preferably, the graphitization degree ≥85%. Controlling the diameter of the cellulose nanofibers to 15-25 nm and the length to >50 μm allows for the formation of a high aspect ratio three-dimensional interlaced framework structure, providing sufficient surface sites for the spread of gallium-based liquid metal. If the diameter is less than 15 nm, the mechanical strength of the fibers is insufficient, making them prone to breakage during preparation and use. If the diameter is greater than 25 nm, the specific surface area of the fibers is too small, making it impossible to achieve uniform spread of gallium-based liquid metal. A graphitization degree greater than 80% ensures the conductivity of the carbon-based framework itself, forming a dual-conductive phase with the gallium-based liquid metal, synergistically improving the overall conductivity of the conductive agent. If the graphitization degree is ≤80%, the conductivity of the carbon-based framework decreases significantly, leading to a reduction in the conductivity of the conductive agent.
[0044] In some embodiments of this application, the carboxyl content of the carbon-based framework is not less than 1.2 mmol / g; preferably, the carboxyl content is 1.2-2.0 mmol / g. A carboxyl content of not less than 1.2 mmol / g in the carbon-based framework provides sufficient reaction sites for the formation of gallium-oxygen-carbon covalent bonds with the gallium-based liquid metal oxide layer, ensuring the strength of the interfacial bonding.
[0045] In some embodiments of this application, the gallium-based liquid metal includes at least one of gallium indium tin alloy, gallium indium alloy, and gallium tin alloy; preferably, the gallium-based liquid metal is a gallium indium tin alloy. Using a gallium indium tin alloy as the gallium-based liquid metal has a low melting point, is liquid at room temperature, and exhibits excellent fluidity and conductivity, as well as good spreading and bonding properties with the carbon-based framework.
[0046] In some embodiments of this application, when the gallium-based liquid metal is a gallium-indium-tin alloy, the gallium content in the gallium-indium-tin alloy is ≥60wt%; preferably, the gallium content is 60-65wt%. A gallium content of not less than 60wt% in the gallium-indium-tin alloy ensures the liquid properties of the alloy and its ability to form a surface oxide layer.
[0047] In some embodiments of this application, the apparent viscosity of the gallium-based liquid metal at 25°C is ≥10. 4 Pa s; preferably, the apparent viscosity is 10 4 -10 5 Pa The apparent viscosity of gallium-based liquid metal at 25°C is not less than 10. 4 Pa This effectively prevents the conductive network from agglomerating and breaking down due to free flow during the use of conductive agents. If the apparent viscosity is below 10... 4 Pa s. Gallium-based liquid metals are too fluid and tend to agglomerate during bending or standing, which can disrupt the continuity of the conductive network.
[0048] It should be clarified that the apparent viscosity of the gallium-based liquid metal mentioned in this application refers to the effective apparent viscosity of the gallium-based liquid metal in the conductive agent composite system after the gallium-based liquid metal and the carbon-based framework form an interpenetrating network, not the bulk viscosity of the pure gallium-based liquid metal. The apparent viscosity is defined according to ASTM D2196 standard, with a shear rate of 10 s⁻¹. - ¹Measured below.
[0049] In some embodiments of this application, the thickness of the gallium-based liquid metal spread along the surface of the carbon-based framework is 80-120 nm; preferably, the spreading thickness is 90-110 nm. Controlling the spreading thickness of the gallium-based liquid metal to 80-120 nm ensures the formation of a continuous conductive network while avoiding metal phase agglomeration due to excessive spreading thickness. If the spreading thickness is less than 80 nm, a continuous liquid metal network cannot be formed, and the conductivity of the conductive agent decreases significantly. If the spreading thickness is greater than 120 nm, the gallium-based liquid metal is prone to agglomeration on the surface of the carbon-based framework, destroying the interpenetrating network structure and increasing raw material costs.
[0050] In some embodiments of this application, the thickness of the oxide layer is 2-3 nm; preferably, the thickness of the oxide layer is 2.0-2.5 nm. Controlling the oxide layer thickness to 2-3 nm ensures the formation of stable gallium-oxygen-carbon covalent bonds with the carbon-based framework while avoiding a decrease in conductivity due to excessive oxide layer thickness. If the oxide layer thickness is less than 2 nm, the oxide layer is discontinuous, unable to effectively block electrolyte penetration, and cannot form uniform covalent bonds. If the oxide layer thickness is greater than 3 nm, the insulation of the oxide layer will reduce the conductivity of the gallium-based liquid metal, affecting the overall conductivity of the conductive agent.
[0051] In some embodiments of this application, the oxide layer includes at least one of Ga2O3 and GaOOH; preferably, the oxide layer is a Ga2O3 / GaOOH mixed oxide layer. The Ga2O3 / GaOOH mixed oxide layer exhibits high reactivity with the carboxyl groups of the carbon-based framework, enabling the rapid formation of stable gallium-oxygen-carbon covalent bonds. Furthermore, the mixed oxide layer exhibits good density and excellent corrosion resistance.
[0052] In some embodiments of this application, the conductivity of the conductive agent is >10. 4 S / m, resistance increase <5% after 100,000 bending cycles; corrosion current density in aqueous electrolyte <10 -8 A / cm². The conductive agent of this application achieves metallic-grade high conductivity through an interpenetrating network structure, while also possessing excellent dynamic stability against bending and resistance to electrolyte corrosion, far surpassing the performance indicators of existing flexible conductive agents.
[0053] Secondly, this application provides a method for preparing the above-mentioned conductive agent. According to an embodiment of this application, the preparation method includes: preparing a carbon-based hydrogel; mixing the carbon-based hydrogel with gallium-based liquid metal droplets and then freeze-drying it to form a porous composite aerogel; and heat-treating the porous composite aerogel at 145-155°C in an inert atmosphere to melt the gallium-based liquid metal and spread it along the surface of the carbon-based framework to form gallium-oxygen-carbon covalent bonds.
[0054] The preparation method of this application is simple and mild. A porous composite aerogel is formed through freeze-drying, providing ample space for the spread of gallium-based liquid metal. Then, heat treatment at 145-155°C achieves the directional spread of the gallium-based liquid metal, while simultaneously integrating the carboxyl groups with the Ga³ oxide layer. + The process involves a dehydration condensation reaction to form interfacial covalent bonds (Ga-OC covalent bonds), requiring no complex equipment or processes. No additional encapsulating agents are introduced during preparation, avoiding loss of conductivity. Furthermore, the high raw material utilization rate makes it suitable for large-scale production, solving the problems of complex and costly existing conductive agent preparation processes. In some embodiments of this application, the steps for preparing carbon-based hydrogels include: oxidizing and modifying cellulose raw materials, followed by homogeneous dispersion to obtain carbon-based hydrogels; preferably, the oxidizing and modifying treatment is TEMPO oxidation treatment, and the homogeneous dispersion is high-pressure homogeneous dispersion. TEMPO oxidation treatment can directionally introduce carboxyl groups onto the surface of cellulose raw materials without damaging the cellulose filament structure, while high-pressure homogeneous dispersion can refine the cellulose raw materials into nanoscale filaments, forming a uniform hydrogel system.
[0055] It should be noted that "TEMPO oxidation treatment" refers to a chemical modification method that uses 2,2,6,6-tetramethylpiperidin-1-oxy (TEMPO) as a nitric oxide radical catalyst, in conjunction with co-oxidants (such as NaClO, KBr, etc.), to selectively oxidize specific functional groups (mainly primary alcohols) under mild conditions.
[0056] In some embodiments of this application, the preparation steps of the gallium-based liquid metal droplets include: dispersing gallium-based liquid metal under an inert atmosphere to form a microdroplet-like dispersed phase; preferably, the dispersion treatment is ultrasonic crushing, and the particle size of the gallium-based liquid metal droplets is 200-500 nm; more preferably, the particle size is 250-450 nm. Ultrasonic crushing under an inert atmosphere can prevent excessive oxidation of the gallium-based liquid metal during dispersion. Controlling the particle size to 200-500 nm ensures uniform dispersion of the droplets in the carbon-based hydrogel, laying the foundation for the subsequent formation of a continuous liquid metal network. If the particle size is less than 200 nm, the surface energy of the droplets is too high, making aggregation likely; if the particle size is greater than 500 nm, the droplets cannot be uniformly dispersed in the carbon-based hydrogel, resulting in a discontinuous conductive network after spreading.
[0057] In some embodiments of this application, the mass ratio of the gallium-based liquid metal droplet to the carbon-based hydrogel is 1:(1-3); preferably, the mass ratio is 1:2. Controlling the mass ratio of the gallium-based liquid metal droplet to the carbon-based hydrogel to 1:(1-3) ensures that the gallium-based liquid metal forms a continuous conductive network after spreading, and prevents agglomeration due to excessive metal phase. If the mass ratio is less than 1:3, the gallium-based liquid metal content is too low, making it impossible to form a continuous conductive network. If the mass ratio is greater than 1:1, the gallium-based liquid metal content is too high, easily leading to agglomeration during spreading and disrupting the interpenetrating network structure.
[0058] As an example, the freeze-drying temperature is -55 to -45°C, and the freeze-drying time is 20-28 hours; preferably, the freeze-drying temperature is -50°C, and the time is 24 hours.
[0059] As an example, the inert atmosphere includes at least one of argon and nitrogen; preferably, it is an argon atmosphere.
[0060] In some embodiments of this application, the heat treatment temperature is 145-155°C; preferably, the heat treatment temperature is 150°C. Controlling the heat treatment temperature at 145-155°C, which is higher than the melting point of gallium-based liquid metal, ensures the melting and directional spreading of the liquid metal, while avoiding excessively high temperatures that could lead to the decomposition of carboxyl groups in the carbon-based framework and the cracking of the oxide layer.
[0061] In some embodiments of this application, the heat treatment time is 0.5-2 hours; preferably, the heat treatment time is 1 hour. Controlling the heat treatment time to 0.5-2 hours ensures that the gallium-based liquid metal spreads sufficiently and forms stable gallium-oxygen-carbon covalent bonds with the carbon-based framework. If the time is less than 0.5 hours, the spreading and bonding reactions are insufficient, resulting in a discontinuous conductive network and weak interfacial bonding. If the time is greater than 2 hours, it leads to excessive oxidation of the gallium-based liquid metal, reducing conductivity and increasing preparation costs.
[0062] Thirdly, this application provides an electrode. According to an embodiment of this application, the electrode includes an active material, a binder, and a conductive agent. The conductive agent includes the conductive agent described in the first aspect, and the amount of the conductive agent added is 3-6 wt%; preferably, the amount of the conductive agent added is 4 wt%.
[0063] The electrode of this application, by adding the aforementioned conductive agent, utilizes the high conductivity and excellent dynamic stability of the conductive agent to maintain a stable conductive path during repeated bending, thereby improving the electrode's cycle performance and rate performance. The amount of conductive agent added is controlled at 3-6 wt%, which can ensure the electrode's conductivity while avoiding a decrease in the proportion of active material due to excessive addition of conductive agent. If the amount added is less than 3 wt%, a continuous conductive network cannot be formed, resulting in poor conductivity and rate performance of the electrode. If the amount added is more than 6 wt%, the proportion of active material decreases, and the electrode's capacity will decrease.
[0064] In some embodiments of this application, the active material includes at least one of polyanionic cathode materials, transition metal oxides, and carbon-based anode materials; preferably, when the electrode is an aqueous sodium-ion battery cathode, the active material is Na3V2(PO4)3. The binder includes at least one of polyvinylpyrrolidone (PVP), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR); preferably, the binder is polyvinylpyrrolidone (PVP).
[0065] In some embodiments of this application, the electrode can withstand 100,000 cycles with a bending radius of ≥5 mm, and the conductivity decays by ≤10% under 10% tensile strain. The electrode of this application possesses excellent flexibility and dynamic stability, meeting the requirements of repeated deformation use in flexible batteries, and is far superior to the performance of existing flexible electrodes.
[0066] Fourthly, this application provides a battery, according to an embodiment of this application, the battery including the electrodes described in the third aspect of this application, and further including a negative electrode, a separator and an electrolyte.
[0067] The battery of this application adopts the above-mentioned flexible electrode and utilizes the excellent properties of the conductive agent in the electrode to enable the battery to have good flexibility, cycle stability and rate performance. It can adapt to various flexible application scenarios such as bending and rolling. Moreover, the battery manufacturing process is compatible with existing battery processes and does not require major modifications to the production equipment.
[0068] In some embodiments of this application, the battery is an aqueous alkali metal ion battery; preferably, it is an aqueous sodium ion battery. The negative electrode includes at least one of a zinc negative electrode, a sodium negative electrode, and a carbon-based negative electrode; preferably, it is a zinc negative electrode. The electrolyte is an aqueous electrolyte, including an aqueous solution of an alkali metal salt; preferably, it is an aqueous solution of a sodium ion salt.
[0069] In some embodiments of this application, the overall thickness of the battery is ≤0.5 mm, the bending fatigue life is ≥50,000 cycles, the capacity retention rate is ≥90% in dynamic bending tests (frequency 1 Hz), and the 5C rate capacity is ≥100 mAh / g. The aqueous sodium-ion battery of this application combines excellent flexibility and electrochemical performance with low raw material costs, making it suitable as an energy storage power source for wearable electronic devices.
[0070] The technical solutions provided in this application will be described in detail below with reference to the embodiments.
[0071] Unless otherwise specified, the raw materials used in the examples and comparative examples are commercially available analytical grade materials.
[0072] Example 1 Example 1 of this application provides a conductive agent, an electrode containing the conductive agent, and an aqueous sodium-ion battery. The specific preparation methods of the three are as follows: 1. Preparation of conductive agents 1) Preparation of carbon-based hydrogel: Microcrystalline cellulose was oxidized by TEMPO and then homogenized under high pressure to obtain a pyrolytic cellulose nanofiber hydrogel with a carboxyl content of 1.2 mmol / g (solid content 1 wt%). The cellulose nanofibers had a diameter of 20 nm, a length of >50 μm, and a graphitization degree of 85%. 2) Preparation of gallium-based liquid metal droplets: Under nitrogen protection, gallium indium tin alloy (Ga content 62wt%) was subjected to ultrasonic crushing at 500 W to form gallium-based liquid metal droplets with a particle size of 300 nm. 3) Mixing and freeze-drying: Carbon-based hydrogel and gallium-based liquid metal droplets are mixed at a mass ratio of 1:2, ultrasonically emulsified to form a homogeneous dispersion, and then vacuum freeze-dried at -50°C for 24 hours to form a porous composite aerogel. 4) Heat treatment: The porous composite aerogel was heat-treated at 150°C for 1 hour in an argon atmosphere to melt the gallium-based liquid metal and spread it in situ along the surface of the cellulose nanofibers. The oxide layer on the surface of the gallium-based liquid metal formed gallium-oxygen-carbon covalent bonds with the carboxyl groups on the surface of the cellulose nanofibers (FTIR 1720 cm⁻¹). - ¹Peak disappearance) yields a conductive agent, wherein the gallium-based liquid metal has a spreading thickness of 100 nm, the oxide layer is a Ga₂O₃ / GaOOH mixed oxide layer with a thickness of 2.5 nm, and the apparent viscosity of the gallium-based liquid metal at 25°C is 5 × 10⁻⁶. 4 Pa s.
[0073] 2. Electrode preparation: The above conductive agent (4 wt%), active material Na3V2(PO4)3 (91 wt%), and binder PVP (5 wt%) are mixed and deionized water is added to form a slurry. The slurry is coated on an aluminum foil current collector and dried to obtain a flexible positive electrode.
[0074] 3. Preparation of aqueous sodium-ion battery: Using the above-mentioned flexible positive electrode as the positive electrode, zinc foil as the negative electrode, glass fiber as the separator, and 1 mol / L Na2SO4 aqueous solution as the electrolyte, a button-type aqueous sodium-ion battery is assembled with an overall battery thickness of 0.4 mm.
[0075] Example 2 The preparation method of this embodiment is the same as that of Example 1, except that: the diameter of the cellulose nanofibers is 15 nm, the particle size of the gallium-based liquid metal droplets is 200 nm, the mass ratio of carbon-based hydrogel to gallium-based liquid metal droplets is 1:1, the thickness of gallium-based liquid metal spreading in the prepared conductive agent is 80 nm, and the thickness of the oxide layer is 2 nm.
[0076] Example 3 The preparation method of this embodiment is the same as that of Example 1, except that: the diameter of the cellulose nanofibers is 25 nm, the particle size of the gallium-based liquid metal droplets is 500 nm, the mass ratio of carbon-based hydrogel to gallium-based liquid metal droplets is 1:3, the thickness of gallium-based liquid metal spreading in the prepared conductive agent is 120 nm, and the thickness of the oxide layer is 3 nm.
[0077] Example 4 The preparation method of this embodiment is the same as that of Example 1, except that: the carboxyl content of the carbon-based skeleton is 1.0 mmol / g, the particle size of the gallium-based liquid metal droplets is 200 nm, the spread thickness of the gallium-based liquid metal in the prepared conductive agent is 70 nm, and the thickness of the oxide layer is 1 nm.
[0078] Example 5 The preparation method in this embodiment is the same as that in Example 1, except that the gallium content in the gallium-based liquid metal is 50 wt%, and the apparent viscosity of the gallium-based liquid metal at 25°C is 5 × 10⁻⁶. 3 Pa The diameter of the gallium-based liquid metal droplets is 580 nm. The thickness of the gallium-based liquid metal in the prepared conductive agent is 130 nm, and the thickness of the oxide layer is 4 nm.
[0079] Comparative Example 1 The preparation method of this comparative example is the same as that of Example 1, except that silver nanowires are used as the conductive agent instead of the conductive agent of this application, and the amount of silver nanowires added is 4 wt%.
[0080] Comparative Example 2 The preparation method of this comparative example is the same as that of Example 1, except that gallium-oxygen-carbon covalent bonds are not formed. The carbon-based hydrogel and gallium-based liquid metal droplets are physically mixed and then directly dried without heat treatment, resulting in a composite conductive agent.
[0081] Comparative Example 3 The preparation method of this comparative example is the same as that of Example 1, except that the gallium-based liquid metal does not form a continuous conductive network.
[0082] Performance testing The conductive agents, electrodes, and batteries prepared in Examples 1-5 and Comparative Examples 1-3 were subjected to performance tests. Unless otherwise specified, the test environment was 25±2°C and 50±5% relative humidity, with three parallel samples in each group, and the results were taken as the arithmetic mean. The specific steps are as follows: Conductivity testing of the conductive agent: The conductive agent is pressed or coated into strips 40 mm long and 10 mm wide. The thickness of the sample is measured, and the sample is placed in an environment of 25±2°C and 50±5% relative humidity for 24 h. The sample is placed on a four-probe test stage with a probe spacing of 1 mm. The test current is gradually increased from 1 mA to 10 mA. The resistance R of each sample is measured at 5 locations: the middle and 10 mm from each end. The conductivity is calculated using σ=L / (R×A), where L is the voltage probe spacing and A is the cross-sectional area of the sample. Three samples are tested in each group, and the average value is taken. The unit is S / m.
[0083] Bending stability test of conductive agent: The two ends of the strip sample are clamped in a reciprocating bending tester. The bending radius is set to 5 mm, the bending angle to 180°, and the frequency to 1 Hz. The sample is continuously bent 100,000 times. The sample is removed before bending and after bending 100, 1000, 10,000, 50,000, and 100,000 times. The resistance Rn is measured using the four-wire method. The resistance increase is calculated as (Rn-R0) / R0×100% based on the resistance before bending, and the curve of resistance increase as a function of the number of bending times is plotted.
[0084] Corrosion resistance test of the conductive agent: The conductive agent was uniformly coated on the surface of a glassy carbon electrode, with the exposed area controlled at 1.0 cm², and dried to serve as the working electrode. A three-electrode system was formed using a platinum sheet as the counter electrode, an Ag / AgCl electrode as the reference electrode, and a 1 mol / L Na₂SO₄ aqueous solution as the electrolyte. After the working electrode was allowed to stand in the electrolyte for 30 min until the open-circuit potential stabilized, a potentiodynamic scan was performed at 1 mV / s within the range of -250 mV to +250 mV, centered on the open-circuit potential. The anodic and cathodic polarization curves were fitted using the Tafel extrapolation method to obtain the corrosion current density, expressed in A / cm². Each test was performed three times.
[0085] Conductivity retention test of the electrode after 10,000 bends: The prepared flexible electrode was cut into 50 mm × 10 mm samples and bent repeatedly 10,000 times under the conditions of a bending radius of 5 mm, a bending angle of 180°, and a frequency of 1 Hz. The resistance R0 before bending and the resistance R10000 after bending were measured using the four-wire method, and the conductivity retention rate was calculated as R0 / R10000 × 100%. Three samples were tested in each group, and the average value was taken.
[0086] 5C rate capacity testing of the battery: The assembled battery was left to stand at 25±2°C for 12 hours, and constant current charge-discharge was performed using a battery testing system within a voltage range of 0.6-1.6 V. First, three activation cycles were performed at 0.1C, followed by five cycles each at 0.5C, 1C, 2C, and 5C. The 5C rate capacity was taken as the average of the specific capacity from the 3rd to the 5th 5C discharge cycles. Specific capacity was calculated by dividing the discharge capacity by the mass of the positive electrode active material, in mAh / g.
[0087] Raw material cost: Record the actual amount of microcrystalline cellulose, gallium-based alloy, TEMPO and other reagents used in the preparation of each group of conductive agents and the purchase price including tax. The raw material cost is calculated as Σ(raw material usage × purchase price) / finished product weight of conductive agent. The result is expressed as the raw material cost required to produce 1 kg of conductive agent, in yuan / kg. Labor, equipment depreciation and energy costs are not included.
[0088] The test results are shown in Table 1.
[0089] Table 1 Test Results
[0090] In Table 1, the conductivity of Examples 1-3 is 1.09 × 10⁻⁶. 4 -1.28×10 4 After 100,000 bends, the resistance increased by 3.2%-4.7%, and the corrosion current density was 6.8 × 10⁻⁶. -9 -8.6×10 -9 With an A / cm², the conductivity retention rate after 10,000 bends is 95.8%-97.2%, and the 5C rate capacity is 99-105 mAh / g, which is better than the comparative examples 1-3.
[0091] The conductivity of Example 4 was 8.2 × 10³ S / m, the resistance increased by 9.6% after 100,000 bends, and the corrosion current density was 2.6 × 10⁻⁶. -8 The A / cm² ratio is lower than that of Examples 1-3 but higher than that of Comparative Examples 1-3.
[0092] Example 5 showed a conductivity of 7.1 × 10³ S / m, a resistance increase of 12.8% after 100,000 bends, and a corrosion current density of 4.2 × 10⁻⁶. -8 The A / cm² ratio is lower than that of Examples 1-3 but higher than that of Comparative Examples 1-3.
[0093] Comparative Example 1 uses silver nanowire conductive agent with a conductivity of 1.2×10³ S / m. After 100,000 bends, the resistance increases by 38.5%, and the raw material cost is relatively high.
[0094] Comparative Example 2, which was not heat-treated and did not form stable interfacial bonds, had a corrosion current density of 3.8 × 10⁻⁶. -7 A / cm², bending stability and corrosion resistance are significantly reduced.
[0095] Comparative Example 3 did not form a continuous liquid metal conductive network, and its conductivity was only 2.1×10³ S / m. After 100,000 bends, the resistance increased by 45.8%.
[0096] The results above demonstrate that the physical constraints of the carbon-based framework, the continuous network of gallium-based liquid metal, and the stable interface between the oxide layer and the carbon-based framework can synergistically improve the conductivity, bending stability, and corrosion resistance of the conductive agent, and improve the rate performance of flexible electrodes and aqueous batteries.
[0097] In the description of this specification, the references to terms such as "one embodiment / mode," "some embodiments / modes," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment / mode or example is included in at least one embodiment / mode or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment / mode or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments / modes or examples. Furthermore, without contradiction, those skilled in the art can combine and integrate the different embodiments / modes or examples described in this specification, as well as the features of different embodiments / modes or examples.
[0098] It should be noted that in this application, relational terms such as "first" and "second" are used merely to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such a process, method, article, or apparatus. Without further limitations, an element defined by the phrase "comprising one..." does not exclude the presence of other identical elements in the process, method, article, or apparatus that includes said element. In this application, "a plurality of" means at least two, such as two, three, etc., unless otherwise expressly specified.
[0099] The above description is merely a specific embodiment of this application, enabling those skilled in the art to understand or implement this application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of this application. Therefore, this application is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features claimed herein.
Claims
1. A conductive agent, characterized in that, It includes a carbon-based framework and a gallium-based liquid metal continuous network spread along the surface of the carbon-based framework; an oxide layer is formed on the surface of the gallium-based liquid metal, and the oxide layer is connected to the surface of the carbon-based framework through gallium-oxygen-carbon covalent bonds to form an interpenetrating network structure.
2. The conductive agent as described in claim 1, characterized in that, The carbon-based framework includes carbon nanofibers; and / or, The carbon nanofibers include cellulose nanofibers; and / or, The cellulose nanofibers have a diameter of 15-25 nm, a length >50 μm, and a graphitization degree >80%; and / or, The carbon-based skeleton has a carboxyl content of not less than 1.2 mmol / g.
3. The conductive agent as described in claim 1, characterized in that, The gallium-based liquid metal includes at least one of gallium indium tin alloy, gallium indium alloy, and gallium tin alloy; and / or, The gallium content in the gallium-based liquid metal is ≥60 wt%; and / or, The gallium-based liquid metal has an apparent viscosity ≥10 at 25°C. 4 Pa·s.
4. The conductive agent as described in claim 1, characterized in that, The thickness of the gallium-based liquid metal spread along the surface of the carbon-based framework is 80-120 nm.
5. The conductive agent as described in claim 1, characterized in that, The oxide layer has a thickness of 2-3 nm; and / or, The oxide layer includes at least one of Ga2O3 and GaOOH.
6. A method for preparing the conductive agent according to any one of claims 1-5, characterized in that, include: Preparation of carbon-based hydrogels; The carbon-based hydrogel was mixed with gallium-based liquid metal droplets and then freeze-dried to form a porous composite aerogel. In an inert atmosphere, the porous composite aerogel is heat-treated at 145-155 °C to melt the gallium-based liquid metal and spread it along the surface of the carbon-based framework, forming gallium-oxygen-carbon covalent bonds.
7. The preparation method according to claim 6, characterized in that, The gallium-based liquid metal droplets have a particle size of 200-500 nm; and / or, The mass ratio of the gallium-based liquid metal droplet to the carbon-based hydrogel is 1:(1-3).
8. The preparation method according to claim 6, characterized in that, The heat treatment time is 0.5-2 h.
9. An electrode, characterized in that, The electrode comprises an active material, a binder, and a conductive agent, wherein the conductive agent comprises the conductive agent as described in any one of claims 1-5, and the amount of the conductive agent added is 3-6 wt%.
10. A battery, characterized in that, The battery includes the electrodes as described in claim 9.